The Effects of Digital Fashion Literacy, Critical Thinking, and Perseverance on Students’ Creative Thinking Ability in Fashion Design Education - Diani Novia Indriati; Ratna Suhartini; Soeryanto Soeryanto; Diani Novia Indriati; Ratna Suhartini; Soeryanto (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Creativity is considered an essential competence in vocational education, particularly in fashion design learning where students are required to generate innovative design ideas and develop original fashion products. However, the development of students’ creative thinking skills is influenced by multiple cognitive and non-cognitive factors. The purpose of this study is to examine the effects of digital fashion literacy, critical thinking, and perseverance on students’ creative thinking ability in vocational fashion education. The study employed a quantitative correlational research design involving 128 eleventh-grade vocational students enrolled in fashion design programs in two public vocational senior high schools located in East Java Province, Indonesia. Information was obtained through questionnaires that participants completed independently without assistance to measure digital fashion literacy, critical thinking, and perseverance, while creative thinking ability was assessed through a performance-based design task evaluated using a structured rubric. Multiple linear regression techniques were employed as the primary statistical method to examine and interpret the dataset with the assistance of Stata MP 17. The results indicate that digital fashion literacy (β = 0.338, p < 0.001), critical thinking (β = 0.182, p = 0.015), and perseverance (β = 0.282, p < 0.001) have positive and significant effects on students’ creative thinking ability. Simultaneously, the regression model explains 33.4% of the variance in creative thinking ability (R² = 0.334). These findings highlight the importance of integrating digital competence, higher-order thinking skills, and perseverance within vocational learning environments to enhance students’ creative potential in fashion design education.